Shaping the future of creative education: the transformative power of VR in art and design learning - Serna-Mendiburu, Gabriela Mariah; Guerra-Tamez, Cristobal Rodolfo (Frontiers in Education, 2024)
Addressing a critical gap in the understanding of virtual reality (VR) in education, this study develops and validates a predictive model to elucidate the influence of usability and spatial ability on learning satisfaction among art and design undergraduates. Utilizing structural equation modeling on data from 105 art and design students in Mexico, we demonstrate that enhanced usability and spatial ability in VR significantly predicts increased learning satisfaction, which in turn, positively affects motivation, cognitive benefits, reflective thinking, and perceived learning. Our findings reveal a direct correlation between VR environment design and educational outcomes, suggesting that meticulous attention to usability and spatial navigation can substantially elevate the learning experience in art and design students. This research contributes to educational technology by offering empirical evidence on optimizing VR for higher education, with implications for curriculum design and pedagogical strategies in creative disciplines.